1998
DOI: 10.1016/s0895-7061(97)00484-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Young Patients After Renal Transplantation Ambulatory Blood Pressure Monitoring Versus Casual Blood Pressure

Abstract: The results of ambulatory blood pressure monitoring (ABPM) in children after kidney transplant were analyzed to ascertain any alteration in circadian BP profile, degree of hypertension, and efficacy of therapy. The data were also compared with casual BP data and left ventricular mass index (LVMI). We have examined 30 patients (17 male, 13 female), mean age 16.1+/-3.6 years after kidney transplant. All patients were receiving triple immune-suppressive therapy and 20 of them were also taking antihypertensive the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 19 publications
6
51
1
3
Order By: Relevance
“…Although this definition neglects influence of hypertension on target organ damage [20], it was shown that ABPM enables detection of increased risk for ventricular hypertrophy in patients whose BP load is above 50% [21]. Investigators have also reported that there was a better correlation of ABPM readings with an increased risk of target organ damage than office BP measurements [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although this definition neglects influence of hypertension on target organ damage [20], it was shown that ABPM enables detection of increased risk for ventricular hypertrophy in patients whose BP load is above 50% [21]. Investigators have also reported that there was a better correlation of ABPM readings with an increased risk of target organ damage than office BP measurements [22].…”
Section: Discussionmentioning
confidence: 99%
“…97 The prevalence of hypertension is even higher with ABPM, approaching 70%-80%. Studies show the prevalence of masked hypertension (normal office BP and elevated ABPM) was 50% greater than that identified using casual BP [98][99][100][101] and an increased prevalence of nondippers among children with kidney transplants. 101,102 A study by Polónia et al 103 concurs with other studies showing significant rates of nocturnal hypertension in pediatric transplant recipients and that a significant proportion of patients thought to be adequately controlled by medications still had masked hypertension.…”
Section: Hypertension In the Pediatric Transplant Recipient Or Recipimentioning
confidence: 94%
“…The use of repeated ambulatory blood pressure monitoring (ABPM) allows us to obtain more representative values of BP and to study the behavior of BP during activity and sleep [19,20,21,22]. Studies have suggested the utility of ABPM in a variety of chronic disease, including diabetes mellitus, postoperative monitoring of surgical repair of coarctation of the aorta, and after kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%